2004
DOI: 10.1007/s10585-004-1867-6
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic breast cancer cells suppress osteoblast adhesion and differentiation

Abstract: Bone is a primary target for colonization of metastatic breast cancer cells. Once present, the breast cancer cells activate osteoclasts, thereby stimulating bone loss. Bone degradation is accompanied by pain and increased susceptibility to fractures. However, targeted inhibition of osteoclasts does not completely prevent lesion progression, nor does it heal the lesions. This suggests that breast cancer cells may also affect osteoblasts, cells that build bone. The focus of this study was to determine the abilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 76 publications
(81 citation statements)
references
References 24 publications
2
78
0
1
Order By: Relevance
“…Despite osteoclast inhibition, bone is not completely repaired or regenerated in breast cancer patients with bone metastases, suggesting an important role for osteoblasts in the progression of disease. There is evidence from clinical and animal studies that bone loss in osteolytic metastasis is partly due to the failure of the osteoblasts to produce the osteoid for bone matrix (Stewart et al, 1982;Sasaki et al, 1995;Mercer et al, 2004). Similarly, administration of bisphosphonates to humans with osteolytic metastasis slows lesion progression but does not bring about healing (Lipton, 2000).…”
Section: Journal Of Cellular Physiology 3 D M O D E L O F B R E a S Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite osteoclast inhibition, bone is not completely repaired or regenerated in breast cancer patients with bone metastases, suggesting an important role for osteoblasts in the progression of disease. There is evidence from clinical and animal studies that bone loss in osteolytic metastasis is partly due to the failure of the osteoblasts to produce the osteoid for bone matrix (Stewart et al, 1982;Sasaki et al, 1995;Mercer et al, 2004). Similarly, administration of bisphosphonates to humans with osteolytic metastasis slows lesion progression but does not bring about healing (Lipton, 2000).…”
Section: Journal Of Cellular Physiology 3 D M O D E L O F B R E a S Tmentioning
confidence: 99%
“…Similarly, administration of bisphosphonates to humans with osteolytic metastasis slows lesion progression but does not bring about healing (Lipton, 2000). Also, in vitro studies have shown that metastatic breast cancer cells increase apoptosis of osteoblasts, suppress osteoblast differentiation and induce an osteoblast inflammatory stress response Mercer et al, 2004). We have previously shown that metastatic breast cancer cells suppress the adhesion and differentiation of osteoblasts .…”
Section: Journal Of Cellular Physiology 3 D M O D E L O F B R E a S Tmentioning
confidence: 99%
“…In vitro, breast cancer cells have been shown to produce soluble factors able to inhibit osteoblast differentiation (20,134), the effect that may be mediated at least in part by the dysregulation of Notch and Wnt developmental signalling pathways. Notch signalling is essential in embryogenesis but has distinct roles in bone homeostasis, regulating the proliferation of immature osteoblasts (135) and suppressing osteoblast differentiation (62,63).…”
Section: Inhibition Of Osteoblasts By Breast Cancer Cellsmentioning
confidence: 99%
“…In addition to promoting invasion, and metastasis of breast cancer, TGF-b secreted by the extracellular bone matrix and osteoclasts suppresses late stages of osteoblast differentiation [3]. It has been shown that metastatic breast cancer cells alter osteoblast adhesion, prevent differentiation, and induce apoptosis, but fas/fas-ligand and TNF-a, two common initiators of cell death, are probably not involved in this aspect of the metastasis/bone cell axis [9,10]. Therefore, bone destruction in metastatic breast cancer results from asynchronous bone turnover wherein increased osteoclastic bone resorption is not accompanied by a comparable increase in bone formation.…”
Section: Biology Of Bone Metastasesmentioning
confidence: 99%